Theoretical Investigation of Friction Welding on Magnesium and Aluminium Alloy. Issue 1 (September 2020) - Kumar, R. Praveen; Rajavel, R.; Navaneethakrishnan, G.
Abstract: In this study, the weld ability of Aluminium Alloys 5083, 6061, 7075 and Magnesium AZ31 was investigated using Friction Welding. Magnesium AZ31 is the base alloy used and other Aluminium alloys were welded with Magnesium Alloy. These Alloys are welded by changing the parameters. Parameters which were used are speed of the spindle, pressure applied during friction, time for which the materials are kept under friction time, Forging Pressure and Forging time. Once the materials are welded by the process of friction welding the weld specimen joints are examined for its changes in its microstructure by the Scanning Electron Microscope (SEM). In order to evaluate the welded specimens mechanical properties the tests such as tensile test and micro hardness tests are carried out. It is found that a specific strength by friction welding method is achieved by aa combination of Magnesium alloy AZ31 along with Alumunium alloys such as 5083, 6061, 7075 by the experimental results.